Ionic Gelatin-Based Flexible Thermoelectric Generator with Scalability for Human Body Heat Harvesting - Shucheng Wang; Liuyang Han; Hanxiao Liu; Ying Dong; Xiaohao Wang (Energies, 2022)
The prosperity of intelligent wearables brings an increasingly critical problem of power supply. Regular rechargeable lithium or disposable button batteries have some problems, such as limited capacity, frequent replacement, environmental pollution, etc. Wearable energy harvester (WEH) can fundamentally solve these problems. Among WEHs, thermoelectric generator (TEG) is a promising option due to its independence of light condition or the motion of the wearer, and thermoelectric conversion (TEC) has the characteristics of quietness and continuity. Therefore, TEG has become a suitable choice for harvesting low-grade heat energy such as human body heat. Ionic thermoelectric gel (iTEG) has the advantages of a large Seebeck coefficient, freely defined shape and size, low processing cost, wide material sources, easy encapsulation, etc. In this paper, the gelatin-based iTEG is regulated and optimized by silica nanoparticles (SiO2 NPs). The optimal compound quantity of SiO2 NPs is determined, and the optimization mechanism is discussed through a series of characterization tests. Based on the iTEG, a kind of scalable flexible TEGs is proposed, and its preparation method is described in detail. A small wristband TEG (STEG) was made, and its Seebeck coefficient is 74.5 mV/K. Its bendability and stretchability were verified, and the impedance matching experiment was carried out. By charging a capacitor, the STEG successfully lights up an LED at a temperature difference (ΔT) of ~15.5 K. Subsequently, a large extended oversleeve TEG (LTEG) was prepared, and a set of heat sinks was added at the cooling end of the LTEG. Being worn on a volunteer’s forearm, the LTEG output a voltage of more than 3 V at ~20 °C. Through storing the converted energy in a capacitor, the LTEG directly drove a calculator without a DC–DC booster. The proposed iTEG and TEGs in this paper have the prospect of mass production, extending to people’s clothes, harvesting human body heat and directly powering wearable electronics.